A 'new normal': Exploring the disruption of a poor prognostic cancer diagnosis using interviews and participant-produced photographs. (September 2015) - Balmer, Claire; Griffiths, Frances; Dunn, Janet
Cancer survival is increasing, and many people are living years after cancer treatment. For example, it is predicted that 46 per cent of men and 56 per cent of women diagnosed in 2007 in England and Wales will survive their cancer for 5 years or more. However, 'survivors' may be living with significant physical, psychological and social disruption caused by their illness. Furthermore, huge disparities exist in the outcomes for different cancer 'types', and there has been little investigation of those living with 'poor prognostic' cancers. Our aim was to explore the experience of living after the diagnosis of a poor prognostic cancer. Data were gathered from 30 people via interviews and participants' own photographs. Our findings suggest that a full 'recovery' may be impossible after a cancer diagnosis. Such diagnoses will continue to threaten biographical trajectory and self-identity forever. 'Returning to normal' was considered highly important for participants, but a changed normality had to be accepted in which lives were managed carefully and a constant fear of recurrence created liminality and made 'survivorship' ambiguous. Experience was often complicated by the social response associated with cancer that hindered communication and increased isolation. Participant-produced photographs, used here for the first time specifically by a sample of people with poor prognosis cancer, proved to be an acceptable data collection method and have added a poignancy and 'completeness' to the data that have arguably led to a more comprehensive understanding.